Models of Parenting and Education in Instilling Character Values: Case Study on Children with Single Parents in Indonesia - Masduki, Yusron; Roviana, Sri; Hopid, Abdul; Yunianti, Fitria Sari; Kistoro, Hanif Cahyo Adi (Dirasat: Human and Social Sciences, 2024)
Objectives: This study seeks to identify single parents’ parenting and educational strategies to instill moral values in their children. Methods: This study applies interviews, observation, documentation, and inductive reasoning. Data validity is performed to determine the level of data validity based on data collection results. The validity of the data relies on credibility by extending participation; specifically, the researcher remains in place until data collection reaches saturation. This is accomplished by observing the daily lives of parents and children in the home, school, and community. Results: The findings show that the authoritarian-democratic single-parenting model is 47%. Single parents tend to provide a mixture of authoritarian and democratic values, in the sense of providing strict and precise parenting based on parental wishes due parental knowledge, education, and occupation. The effects of parenting by parents include obedience, discipline, fear of punishment, introversion, diminished creativity, communication, independence, and respect for others. Conclusions: Single parents are responsible for their child’s physical and mental development. Parents’ attention and affection are irreplaceable. The motivation and example of parents must be instilled more so that children continue to receive their parents’ love and attention. Parents who invest time and care in their children can instill a positive character and personality. Also, parents must teach them that they are a family who can serve as role models and a support system in times of difficulty.